The innocence of Omicron: Taking the right decision - Dhar, Ruby; Kumar, Arun; Karmakar, Subhradip (Asian Journal of Medical Sciences, 2022)
Rapidly spreading Omicron (B1.1.529) poses a considerable health risk, despite being labeled as a mild SARS-CoV2 variant. The higher transmissibility, immune evasion properties along blunting the effect of vaccine are some of its unique features, a fact that should not be ignored, no matter how benign it might be. We suggest that our knowledge and experience in dealing with Omicron have been very less and its long-term health consequences are still not studied properly. Under these conditions, we must continue to remain vigilant following all safety measures and avoid down-sizing its impact.